Neyse halim çiksin falim - Gürsel, Zeynep Devrim (United States : Gürsel, Zeynep Devrim ; Gürsel, Umut, 2009)
"Coffee Futures" weaves individual fortunes with the story of Turkey's decades-long attempts to become a member of the European Union. Promises and predictions made by politicians, both foreign and domestic, are juxtaposed with the rhetoric and practices of coffee fortune-telling. The widespread custom of coffee fortunetelling in Turkey is an everyday communication tool. Coffee fortunes are a way of dealing with hopes, fears and worries, as well as a method of indirectly voicing matters usually left unspoken. The filmmaker flips her cup for dozens of people, both friends and strangers. These amateur fortune tellers all read her individual fortune as they might any other day, except that she also asks for their opinions on the future of Turkey and Europe. Coffee Futures attempts to render the emotional texture of a society whose fate has been nationally and internationally debated, often in relation to Europeaness, over a very long period of time, to hint at the psychology of collective waiting and anticipating a national future.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films